NILAI-NILAI PERJUANGAN NOVEL SAGARAS KARYA TERE LIYE - M. Husni Mubarok (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the values ​​of struggle in the novel Sagaras by Tere Liye, using a sociology of literature approach. This study is a qualitative literature study. The data sources used are quotations containing the values ​​of struggle in the novel Sagaras by Tere Liye. The data collection technique in this study uses documentation studies, searching for or finding data about things or variables in the form of notes or quotations, transcripts, books, newspapers and so on. The data analysis technique used is the document review technique, by recording important contents in the document using the content analysis method, data reduction method, and interpretation method. The results of this study are the values ​​of struggle which overall there are 53 data, from each of these struggle values ​​there are 5 values ​​of struggle, including the value of willingness to sacrifice there are 8 data, the value of unity 14 data, the value of respect 14 data, the value of enthusiasm and never giving up 14 data and the value of cooperation 6 data. The five values ​​of struggle are then studied for their benefits in solving various problems faced. In its application, the researcher explains the benefits of the values ​​of struggle to be applied in community life or in the world of education to build national character based on struggle so as not to give up easily, and not cause division among each other. Especially in the values ​​of struggle contained in the novel Sagaras by Tere Liye.